Reserves for all? Central bank digital currency, deposits, and their (non)-equivalence - Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2018)
I offer a macroeconomic perspective on the "Reserves for All" (RFA) proposal to let the general public use electronic central bank money. After distinguishing RFA from cryptocurrencies and relating the proposal to discussions about narrow banking and the abolition of cash I propose an equivalence result according to which a marginal substitution of outside for inside money does not affect macroeconomic outcomes. I identify key conditions on bank and government (central bank) incentives for equivalence and argue that these conditions likely are violated, implying that RFA would change macroeconomic outcomes. I also relate my analysis to common arguments in the discussion about RFA and point to inconsistencies and open questions.
Keywords: E42; E51; E58; E61; E63; H63; 330; central bank digital currency; Fedcoin; CADcoin; e-krona; e-Peso; J Coin; reserves for all; deposits; narrow banking; cash; equivalence; central bank; lender of last resort; politico-economic equivalence